2011
DOI: 10.1159/000330838
|View full text |Cite
|
Sign up to set email alerts
|

Thin Bronchoscope for Evaluating Stenotic Airways during Stenting Procedures

Abstract: Background: Flexible bronchoscopy can play an important role in the evaluation of an airway lumen during therapeutic bronchoscopic procedures. Despite its potential usefulness, however, evaluation with a standard-sized bronchoscope, which cannot pass completely through a severely stenosed airway, is often unsatisfactory. Objectives: This study aimed to evaluate the usefulness of prototype thin bronchoscopes for assessing stenotic airways during stenting procedures. Methods: Forty-six patients with central airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Conventional thin bronchoscopes less than 3.9 mm in external diameter equipped with a 1.2-mm working channel, 18,19 and eventually thin bronchoscopes with a 1.7-mm working channel which allow the use of a thin radial ultrasonic probe have recently been developed. 9,10,20 In a former preliminary study, 9 we demonstrated that the diagnostic yield of EBUS-TBB with the thin bronchoscope for peripheral pulmonary lesions with a mean size of 31 mm was 69%. The results of this study are consistent with those of the former preliminary study.…”
Section: Discussionmentioning
confidence: 88%
“…Conventional thin bronchoscopes less than 3.9 mm in external diameter equipped with a 1.2-mm working channel, 18,19 and eventually thin bronchoscopes with a 1.7-mm working channel which allow the use of a thin radial ultrasonic probe have recently been developed. 9,10,20 In a former preliminary study, 9 we demonstrated that the diagnostic yield of EBUS-TBB with the thin bronchoscope for peripheral pulmonary lesions with a mean size of 31 mm was 69%. The results of this study are consistent with those of the former preliminary study.…”
Section: Discussionmentioning
confidence: 88%
“…Cases where the bronchus beyond the segmental bronchus was invaded and obstructed (e.g. cases with the tumour extending from the peripheral bronchus) were revealed by flexible bronchoscopes [11], and we did not consider as having indications for stenting. The size and length of the stent are decided using a flexible bronchoscope, endobronchial ultrasound with a balloon and pre-procedural computed tomography as previously described [12].…”
Section: Methodsmentioning
confidence: 99%
“…Silicone stents can be straight or bifurcated for stenoses that involve the carina or primary right carina (Oki stent) (106,114). The diameter and size are chosen based on scanographic and per-operative bronchoscopic data, which are then adjusted by cutting (37,75,108,(115)(116)(117).…”
Section: Silicone Stentsmentioning
confidence: 99%